Investigation the structures CdSe/CdS, CdS/CdSe for production of solar cells - Guminilovych, Ruslana; Shapoval, Pavlo; Yatchyshyn, Yosyp; Kusnezh, Viktor; Sozanskiy, Martyn; Il’chuk, Hryhoriy (Видавництво Львівської політехніки, 2013)
The process of obtaining CdS and CdSe thin films by a chemical surface deposition method (CSD) has been investigated. The optical transmission, absorption spectra, surface morphology of films and degree of phase uniformity, crystallinity of structures based on CdS and CdSe films have been studied.
Keywords: semiconductor films; chemical surface deposition; structure and morphology of thin films; solar cells